On place adverbials ČIA end TEN in East Aukštaitian Utena subdialect - Judžentytė, Gintarė (Lietuvių kalba, 2011)
The article deals with one case of the usage of the adverbs of place čia and ten in East Aukštaitian Utena dialect (to be more precise, the dialect used at the boundary of North East Aukštaitian Vilnius and Utena). The aim of the article is to analyse the meanings of the adverbs of place čia and ten used in deictic situations on the basis of Karl Bühler’s theory of deixis. The analysis of dialectal texts has revealed that: 1. Apart from the main meanings of ‘in this place’ and ‘in a further place’, in this sub-dialect the adverbs of place čia and ten, when accompanied by gestures, acquire other meanings: depending on which side the speaker is pointing to, they may refer to the right and the left side. This conclusion is based on the following reasons: a) in direct deixis, adverbs of place referring to the right and the left side are not necessary since the speaker may show to the objects seen by the interlocutor using his/her hand; b) in the case of imaginary deixis the addresser projects the reality from his own perspective, therefore in this situation čia and ten, when accompanied by gestures, may also mean both the right and the left side; c) in the case of anaphora adverbs čia and ten function as substitutes and may also refer to a place in either the left or the right side. 2. When adverbs čia and ten acquire the meanings of ‘right’ and ‘left’, the correlation of distance between them disappears: from the perspective of origo, they both refer to a place further, to the right or to the left. 3. Adverbs of place meaning left or right (dešinėj, dešinėjè, dešinėn, iš dešinės, po dešine, po dešinei, kairėj, kairėjè, kairėn, iš kairės, po kaire, po kairei) should be treated as deictic, because: a) they are used synonymously together with adverbs of place čia and ten accompanied by a gesture; b) they are directly related to origo, i.e. refer to a place in either one or the other side. 4. The studies carried out lead to a conclusion that the adverbs of place under investigation are used under the same linguistic circumstances in the Lithuanian language in general.